2000
DOI: 10.1614/0890-037x(2000)014[0030:wcapst]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Weed Control and Potato (Solanum tuberosum) Yield with Banded Herbicides and Cultivation1

Abstract: Experiments compared the effect on weed control and potato yield of banded applications of metolachlor plus linuron with or without flex-tine, rolling, and shovel cultivation prior to hilling. Cultivation without banded herbicide resulted in greater prehilling in- and between-row weed densities and reduced late-season weed control as compared to broadcast herbicides or cultivation with banded herbicides. Although the flex-tine and rolling cultivators were expected to provide improved in-row weed control, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
3
8
0
1
Order By: Relevance
“…There was a trend of greater reduction in dry weight of quackgrass and corn spurry with cultivation at 28 DAP compared to the two other times of cultivation; however, this difference was not significant. These results are comparable to those of Belinder et al (2000), who reported more weeds present in the cultivated treatments compared with the herbicide treatments. Delaying cultivation for an additional 7 d (28 DAP) or 14 d (35 DAP) resulted in less reduction in dry matter and provided support for the findings of Van Gressel and Renner (1990b) that hilling at emergence gave the best weed control, presumably because weeds were smaller when cultivated at potato emergence and as a result were easier to up-root or cover with soil.…”
Section: Results and Discussion Weed Controlsupporting
confidence: 85%
See 1 more Smart Citation
“…There was a trend of greater reduction in dry weight of quackgrass and corn spurry with cultivation at 28 DAP compared to the two other times of cultivation; however, this difference was not significant. These results are comparable to those of Belinder et al (2000), who reported more weeds present in the cultivated treatments compared with the herbicide treatments. Delaying cultivation for an additional 7 d (28 DAP) or 14 d (35 DAP) resulted in less reduction in dry matter and provided support for the findings of Van Gressel and Renner (1990b) that hilling at emergence gave the best weed control, presumably because weeds were smaller when cultivated at potato emergence and as a result were easier to up-root or cover with soil.…”
Section: Results and Discussion Weed Controlsupporting
confidence: 85%
“…In recent years, increased public concern about the use of pesticides in crop production has intensified research efforts to find ways to reduce the amount of herbicides applied in potato production. Belinder et al (2000) examined weed control in potatoes using banded herbicides and different types of cultivation equipment. They found that pre-hilling weed densities were greater with cultivation equipment than with broadcast herbicide or banded herbicide + cultivation, but potato yields were not reduced by this greater weed density.…”
mentioning
confidence: 99%
“…Weed control can be accomplished with an integration of different methods (chemicals at low doses, agronomic, mechanical, cultural), which by themselves are only partially suppressive, but together can act against the same individuals or synergistically against different individuals in order to achieve an acceptable and stable level of weed control (Paolini, 1996). From an integrated weed management perspective, the choice of a more competitive cultivar (cultural method) can be a low-cost method to enhance the efficacy of other weed control means, such as chemical control at low doses (Bellinder et al, 2000), reduced mechanical control or other cultural and agronomic methods (Ferrero & Vidotto, 1998;Liebman & Davis, 2000;Bond & Grundy, 2001;Ba`rberi, 2002). Moreover, as options for biological control are limited (Hallett, 2005), a complete reliance on mechanical control is undesirable (Bastiaans et al, 2008), and choosing a more competitive cultivar seems particularly relevant for organic agriculture in order to improve crop competitiveness.…”
Section: Introductionmentioning
confidence: 99%
“…A aplicação de herbicidas em pós-emergência com ou sem efeito residual no PCPI, bem como o método de controle pela utilização de cultivadores no período da amontoa, além do sistema de rotação de culturas e que utiliza a cobertura morta combinada com herbicidas, destacariam-se como excelentes alternativas de manejo da comunidade de plantas daninhas na cultura da batata (Liebman et al, 1996;Eberlein et al, 1997;Bellinder et al, 2000;Bailey et al, 2001;Boydston & Vaughn, 2002;Hutchinson et al, 2003). Desta maneira, Knezevic et al (2002) e Zoschke & Quadranti (2002) ressaltam que o manejo integrado de plantas daninhas com o uso de diferentes téc-nicas para prever os problemas causados por essas espécies e, assim, antecipar o manejo principalmente quando já estão presentes, convivendo com a cultura poderia contribuir para prevenção de produção de semente e reduzir a germinação, além de minimizar a competição entre as plantas daninhas e a cultura, porém sem eliminar completamente as plantas invasoras.…”
Section: Os Valores De X Corresponderam a 20unclassified